Improving the system using the bee algorithm and the ant algorithm and comparing them (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In The allocation of reliability and optimization for each part of the complex system has been determined in this paper, in order to solve the problem of allocation and to improve network stability we will use Bees Colony Optimization (BCO) and the ant colony optimization (ACO) algorithm. The three cost functions are also introduced (exponential behavior with feasibility factor model, exponential behavior model and logarithmic model). After solving the allocation problem. The aim of this paper is to compare the effects of the three cost functions using Bees Colony algorithm and the ant colony optimization algorithm in terms of reliability allocation and optimization to determine which is more efficient